PENGARUH POLYVINYL ACETATE (PVAC) TERHADAP KUAT TEKAN MATERIAL NANOKOMPOSIT DARI TANDAN KELAPA SAWIT - Ida Sriyanti; Leni Marlina (Universitas Sriwijaya, 2014)
The aims is to determine the effect of filler Mg(OH)2 against pressing pressure nanocomposite material bunches of palm oil that has been made. The method used in this study is a simple method of mixing and hot press method. Presses temperatures used in this study was 100 ° C, the time press was 15 minutes and pressing pressure was 50 MPa. To determine the feasibility of the nanocomposite material has been made by characterization with the pressing test. From the pressing test results obtained to the highest pressing presure when the composition ratio of waste oil palm empty fruit bunches (TTKS), PVAc, Nonosilika is 13:2 : 0,75 (gr) with the pressing presure as big as 55 MPa, while the composition ratio of the composite without giving PVAc obtained pressing presure as big as 22.5 MPa. This research method is very useful to produce a material that is strong and light nanocomposite in a short time interval.